Catástrofe y no catastrofismo en las poéticas de Benedetti, Gelman, Hahn y Romero (Altre Modernità, 2013)
Which significant expressive singularities can be pointed out in the poetic expression of apocalyptic issues in Southern Cone Spanish American poetry? This paper focuses on the poetics of four authors who produced part of their work in exile, as a result of apocalyptic XXth Century dictatorships in the Latin-American Southern Cone: Mario Benedetti (Uruguay), Juan Gelman (Argentina),Oscar Hahn (Chile) and Elvio Romero (Paraguay). Our thematic approach does not concentrate on the Biblical Apocalypse or St John´s myths in literature, but, rather, on the poetic expressions of historical ruptures or extraordinary disasters. The paper takes into account the notion of (poetic) constellation (Monteleone, 2003 & 2010) to explain the non-exhaustivity of the group of poetics and the relevance of considering these four formally dissimilar poetics together. A synthetic characterization of each of the poetics is presented, based on well-known critical studies, discussing and exemplifying: neo-manierism and elements of fantasy literature in Hahn´s poetry; torrential wordiness and symbolism in Gelman´s poetry; “realism” and songs of heroic deeds in Romero´s poetry and “humorous” colloquialism in Benedetti´s poetry. Finally, using Discourse Studies, mainly, the interdiscourse concept (Foucault, [1969]2012; Pêcheux, [1990]2009), we show that, despite the underlying differences between the four poetics, two points of convergence can be pointed out: non-catastrophism and the universal approach of (even local) issues pervading the constellation composed by those four poetic expressions.
Keywords: Poesia; Benedetti; Gelman; Hahn; Romero; Catástrofe